2010
DOI: 10.1002/jor.21167
|View full text |Cite
|
Sign up to set email alerts
|

Circulating plastic adherent mesenchymal stem cells in aged hip fracture patients

Abstract: ABSTRACT:We examined the presence of circulating plastic adherent multipotent mesenchymal stem cells (MSCs) in fracture patients. Three patient groups (n = 10-18) were evaluated, including elderly females with a femoral neck fracture treated with cemented hemiarthroplasty, an age-and sex-matched group with hip osteoarthritis (OA) treated with cemented total hip arthroplasty (THA), and younger adults with surgically treated lower extremity fractures. The presence of circulating MSCs pre-and postoperatively was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 28 publications
7
99
0
1
Order By: Relevance
“…This new paradigm uses pharmacologic induction of mobilization and endogenous mechanisms of cell homing and engraftment to sites of injury. It is plausible this strategy simply mimics and amplifies normal repair mechanisms as progenitor cells are mobilized to the PB after stroke [41], vascular trauma [20], musculoskeletal trauma [31,32], fracture [3,34], distraction osteogenesis [34], and myocardial infarction [60]. An important pathway for stem cell mobilization is the SDF-1/CXCR4 axis and there are recent data supporting the concept that transient disruption of this receptor-ligand complex through the CXCR4 antagonist, AMD3100, enhances bone formation in vivo [57,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new paradigm uses pharmacologic induction of mobilization and endogenous mechanisms of cell homing and engraftment to sites of injury. It is plausible this strategy simply mimics and amplifies normal repair mechanisms as progenitor cells are mobilized to the PB after stroke [41], vascular trauma [20], musculoskeletal trauma [31,32], fracture [3,34], distraction osteogenesis [34], and myocardial infarction [60]. An important pathway for stem cell mobilization is the SDF-1/CXCR4 axis and there are recent data supporting the concept that transient disruption of this receptor-ligand complex through the CXCR4 antagonist, AMD3100, enhances bone formation in vivo [57,59].…”
Section: Discussionmentioning
confidence: 99%
“…Alm et al [3] found circulating plastic-adherent MSCs are more common in patients after fracture than in subjects who had not fractured. Lee et al [35] reported an increase in circulating EPCs after tibial fracture in female BALB/c mice, peaking at Day 3 postfracture, while Laing et al [31] report a slightly early time course in response to tibial fracture in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…6 Ce phénomène a également été observé en clinique chez des patients âgés après une fracture traumatique de la hanche. 7 Les CSM en tant que traitement 'prêt à l'usage' Les cellules stromales mésenchymateuses peuvent être mises en culture et proliférer de façon considérable dans un environnement in vitro, indépendamment de leur source tissulaire. Lorsque leur nombre est suffisamment élevé, les CSM allogéniques peuvent être traitées et administrées à un patient sans vérifier la compatibilité croisée.…”
Section: Que Sont Les Cellules Stromales Mésenchymateuses?unclassified
“…6 A similar mobilization of MSCs into the circulation has also been observed clinically in elderly patients following traumatic hip fracture. 7 MSCs as an ''off-the-shelf'' therapy Mesenchymal stromal cells can be cultured and significantly proliferate in vitro irrespective of the tissue source. When expanded to sufficient numbers, allogeneic MSCs may be processed and administered to a patient without cross-matching.…”
mentioning
confidence: 99%
“…As MHC II and costimulatory molecules are not expressed on MSCs it is hypothesized that allogeneic MSCs may be of use in the treatment of inflammatory conditions, such as RA [9][10][11]. Furthermore, evidence suggests that MSCs may preferentially migrate to sites of tissue injury, such as bone fractures and metastatic disease in vivo [12,13]. Despite this, it has not been consistently demonstrated that MSCs have a therapeutic role in murine models of inflammatory arthritis.…”
Section: Introductionmentioning
confidence: 99%